(untitled) (Филологические заметки, 2019)
The case in point in the article is the question of medical metaphor as one of the most active models in modern Russian and Bulgarian media discourses. Medical metaphor is not a new metaphorical model. It has been known since antiquity. It’s conceptual scope of the source is ’medicine, illness’. Today this metaphor demonstrates the problems and the painful conditions of the society, diagnosis and even prescribes treatment for them. With this metaphor modern media is drawing well the problems that arise in society and requires an immediate solution. Medical metaphor seems to be one of the most emotional forms of influence on readers. However, an equivalent representation of the model ’policy - a disease’ in Russian and Bulgarian political discourse, the model ’policy - medicine’ is more structured in Russian media texts.